(untitled) (inOpera Esercizi di lettura su testi contemporanei, 2025)
The article proposes a metapoetic interpretation of Fissità, a poem that, at first glance, does not seem to have a distinct metadiscursive nature. To support this interpretation, three recurring themes in Sereni’s poetry are examined: the liminal landscape, friendship, and sewing. Several poems from Stella variabile are analysed to reveal the metapoetic dimension of these themes, highlighting the metapoetic imagery the author constructs throughout the book. The analysis concludes with Fissità, a poem that embodies all three metapoetic themes. This brings to light an implicit reflection on poetry, suggested by the described landscape, the unspoken interlocutor (Fortini), and the mending performed by the encountered character – an allegory of the fragile yet persistent nature of the poetic act.